ONLINE GRAMMAR CHECKERS AND THEIR USE FOR EFL WRITING - Iwan Perdana; Muthia Farida (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2019)
The presence of online grammar checkers as the result of technology advancement is inevitable to be popular among academicians and researchers. With more complete features offered to help improving writing, many utilize these tools to accomplish their work. This paper, thus, aims to present an overview of online grammar checkers and their use for EFL writing. Specifically, this paper explicates online grammar checkers and reviews some research investigating the use of these applications for writing. In addition, brief reviews about a number of online grammar checker tools comprising Grammarly, ProWritingAid, Ginger, and GrammarCheck are provided. Last, some suggestions are also offered for teachers and future researchers regarding the use of online grammar checkers.